Wherefore art thou competitors? How situational affordances help differentiate among prosociality, individualism, and competition - Liu, Y. (2025)
The Triple Dominance Measure (choosing between prosocial, individualistic, and competitive options) and the Slider Measure ("sliding" between various orientations, for example, from individualistic to prosocial) are two widely used techniques to measure social value orientation, that is, the weight individuals assign to own and others' outcomes in interdependent situations. Surprisingly, there is only moderate correspondence between these measures, but it is unclear why and what the implications are for identifying individual differences in social value orientation. Using a dataset of 8021 participants from 31 countries and regions, this study revealed that the Slider Measure identified fewer competitors than the Triple Dominance Measure, accounting for approximately one-third of the non-correspondence between the two measures. This is (partially) because many of the Slider items do not afford a competitive option. In items where competition is combined with individualism, competitors tended to make the same choices as individualists. Futhermore, we demonstrated the uniqueness of competitors. Compared to prosocials and individualists, competitors exhibited lower levels of both social mindfulness and trust. Overall, the present work highlights the importance of situational affordances in measuring personality, the benefits of distinguishing between individualists and competitors, and the importance of utilizing a measure that distinguishes between these two proself orientations.